The Influence of Workload, Work Environment, and Work Ethic on Service Quality at BaliMed Karangasem Hospital - Dicky Dicky; Susiana Nugraha; Karlina Isabella; Ignatius Erik Sapta Yanuar (Journal of Ageing And Family, 2024)
The quality of service in hospitals is one of the important factors that influences patient satisfaction and hospital operational efficiency. Workload, work environment, and work ethic are factors that can influence the quality of services provided by health workers. Excessive workload can cause stress and fatigue, while a supportive work environment and good work ethic can increase employee motivation and performance. This study aims to analyze the influence of workload, work environment, and work ethic on the quality of service at BaliMed Karangasem Hospital. The method used was analysis using primary data obtained through questionnaires distributed to 122 respondents, consisting of nurses and midwives. The analysis used includes univariate, bivariate, and multivariate analysis. The research results showed that the majority of respondents had a high workload (78.7%), a good work environment (75.4%), a good work ethic (86.1%), and good service quality (76.2%). In multivariate analysis, workload (AOR=7.271, p=0.006) and work ethic (AOR=7.243, p=0.002) were found to have a significant influence on service quality, while work environment did not have a significant influence. The results of this research suggest that hospitals pay attention to managing workloads in a more balanced manner and support increasing work ethics to improve the quality of services provided to patients. Future research is recommended to explore other factors that can influence service quality, such as management support and skills training.